A rare case of docetaxel‐induced myositis in a patient with a lung adenocarcinoma. Issue 14 (20th May 2022) - Ishida, Akane; Ushio, Ayumi; Hashimoto, Masao; Ishii, Satoru; Naka, Go; Iikura, Motoyasu; Izumi, Shinyu; Hojo, Masayuki; Sugiyama, Haruhito
Abstract: Docetaxel is a cytotoxic taxane frequently used to treat patients with various cancers, including non‐small cell lung cancer (NSCLC). Docetaxel is known to cause acute myalgias, arthralgias, and neuropathy, but there have been few published case reports of myositis. Here, we describe a rare case of docetaxel‐induced myositis diagnosed based on laboratory data, thigh magnetic resonance imaging (MRI), and electromyography (EEG). A 66‐year‐old male was admitted for thigh pain and fatigue that onset 1 week prior. He had been diagnosed with stage IVA (cT4N0M1a) NSCLC 3 years ago and had been started on docetaxel (60 mg/m 2 intravenously every 3 weeks; fourth‐line chemotherapy) 1 month earlier. After the second cycle, he developed both thigh pain and fatigue. On admission, his creatinine phosphokinase (CPK) level was elevated, thigh MRI revealed diffuse muscle edema, and EEG showed myogenic changes. We found no plausible cause for myositis except docetaxel. He was diagnosed with myositis and treated with oral prednisolone. His symptoms were relieved and the CPK level declined. Although rare, this case indicates that clinicians should consider the possibility of myositis as a complication in patients on docetaxel. Abstract : Docetaxel, a cytotoxic taxane frequently used to treat patients with various cancers, is known to cause acute myalgias, arthralgias, and neuropathy, but there have been few case reports of myositis. We describe a case of docetaxel‐induced myositis that developed after two cycles of docetaxel, and diagnosed based on laboratory data, thigh magnetic resonance imaging, and electromyography. Clinicians should consider this possibility when patients complain of muscle pain or the CPK level is elevated. Docetaxel‐induced myositis developed after two cycles of docetaxel in a patient with a lung adenocarcinoma.